Incidencia del factor de conversión de potencia hidráulica en la solución del problema del despacho hidrotérmico de mínimo costo (2008)
The reliability of the solution obtained for the hydrothermal economic dispatch problem directly depends on the exactitude shown by the estimate value of the hydraulic power when it is resolved by mixed binary linear programming. Such level of exactitude can be measured based on the average relative error. This error increases as the percentage variation grows between hydraulic power conversion factors (max. and min. value). This article confirms the impact that such percentage difference has had in the reliability of the obtained solution. Consequently, five tangible examples have been exposed. Each one of them refers to a company satisfying an energy demand in a medium term planning horizon. In addition, the company must have possession of one hydroelectrical and two thermal generation centers.